EFEKTIFITAS MEKANISME TRANSMISI KEBIJAKAN MONETER PADA JALUR SUKU BUNGA PERIODE 2005:07-2010:06 - Muhammad Alfian (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2011)
Vector Auto Regression (VAR) is an analysis or statistic method which can be used to predict time series variable and to analyst dynamic impact of disturbance factor in the variable system. In addition, VAR analysis is very usefull to assess the interrelationship between economics variable. This research through the following test phases: unit root test, optimal lag test, granger causality test, and form a vector auto regression model (VAR). The data used in this research is the Bank Indonesia Certificate rate data (SBI), interbank offered rate data (PUAB), deposit rate data (DEP), loan rate data (KDRT) and credit aggregate data (AGKDRT) of Indonesia in the period 2005:07-2010:06. The effectiveness was measured by two indicators. They are: (1). how fast or how many time lag needed since the shock of monetary instruments (rSBI) until the realisation of intermediary target of monetary policy (monetary aggregate). (2). How strong the variables of Interest Rate Channel response the shock of SBI interest rate and other variable. This study used secondary data issued by Bank Indonesia. The result of the study shows that response velocity of variable in Interest Rate Channel towards shock instrument of monetary policy (SBI) until reach the final target about 4 months. While impulse response function of variables in this channel to the shock instrument of monetary policy (SBI) is quiet weak and the main variable in interest rate money market among bank (PUAB) able to explain diversity intermediary target of monetary policy (Monetary Aggregate) about 2,82%. This result once shows a weak Granger causality and predictive power between PUAB as the operational target with monetary aggregate as the intermediary target of monetary policy. Thus we can conclude that mechanism of monetary policy transmission through Interest Rate Channel is not effective to reach the intermediary target of monetary policy of Indonesia period of 2005:072010:06. Keyword: Vector Auto Regression (VAR), The Monetary Transmission Mechanism (MTKM), The Interest Rate Channel.